Prospects for the use of various sugars to produce fondant with reduced glycemicity - Dorozhynska (Onofriichuk), Oksana; Kokhan, Olena; Okoрna, Yana (My University, 2019)
The thesis shows the results of research on the improvement of the technology of unglazed crystalline structure sweets, which are made without the introduction of traditional sugar - sucrose. The advantages of using innovative tagatose sugar in the production of confectionery are analyzed. The influence of tagatose on the parameters of the process of fondant formation and product formation is investigated. It is proposed to increase the dosage of starch molasses and additionally introduce hygroscopic fructose to extend the shelf life of finished products.
Keywords: помадні цукерки; глікемічний індекс; тагатоза; замінник цукру; кристалізація; цукровий діабет; fondant sweets; glycemic index; tagatose; sugar substitute; crystallization; diabetes; кафедра технології хлібопекарських і кондитерських виробів; кафедра іноземних мов професійного спрямування